The role of the "champion" in infection prevention: results from a multisite qualitative study. Issue 6 (2nd December 2009) - Damschroder, L J; Banaszak-Holl, J; Kowalski, C P; Forman, J; Saint, S; Krein, S L
Abstract : Background: Although 20% or more of healthcare-associated infections can be prevented, many hospitals have not implemented practices known to reduce infections. We explored the types and numbers of champions who lead efforts to implement best practices to prevent hospital-acquired infection in US hospitals. Methods: Qualitative analyses were conducted within a multisite, sequential mixed methods study of infection prevention practices in Veteran Affairs and non-Veteran Affairs hospitals in the USA. The first phase included telephone interviews conducted in 2005–2006 with 38 individuals at 14 purposively selected hospitals. The second phase used findings from phase 1 to select six hospitals for site visits and interviews with another 48 individuals in 2006–2007. Results: It was possible for a single well-placed champion to implement a new technology, but more than one champion was needed when an improvement required people to change behaviours. Although the behavioural change itself may appear to be an inexpensive and simple solution, implementation was often more complicated than changing technology because behavioural changes required interprofessional coalitions working together. Champions in hospitals with low-quality working relationships across units or professions had a particularly challenging time implementing behavioural change. Merely appointing champions is ineffective; rather, successful champions tended to be intrinsically motivated and enthusiastic about the practices they promoted. Even when broad implementation is stymied, champions can implement change within their own sphere of influence. Conclusions: The types and numbers of champions varied with the type of practice implemented and the effectiveness of champions was affected by the quality of organisational networks.